Bio-inspired 4D printed intelligent lattice metamaterials with tunable mechanical property - Zhang, Xinchun; Han, Yuesong; Zhu, Min; Chu, Yuhao; Li, Weiduan; Zhang, Yanpeng; Zhang, Yan; Luo, Junrong; Tao, Ran; Qi, Junfeng (International journal of mechanical sciences, 2024)
•Intelligent metamaterials are developed by bio-inspired design concept and 4D printing method.•A novel theoretical calculation model of coupling of intelligent material and structure is proposed.•Tunable mechanical properties are verified by theoretical calculation, experiments and finite element analysis.•Various mechanical properties are large-scale controlled by regulating parameters and temperature. 4D-printed intelligent metamaterials possess a multitude of potential applications in the engineering fields due to their novel structures and functions. In this paper, a multifunctional intelligent metamaterial inspired by arc-bearing structure in human spine and tortoise shell has been established based on 4D printing technology. The innovative metamaterial exhibits programmable shape, significantly tunable mechanical properties, reusable characteristics with good loading, energy absorbing and vibration damping ability. Theoretical models of the metamaterial are developed to describe its intelligent mechanical properties. The relationship between structural parameters and the temperature field in relation to the tunable mechanical properties and functionalities of metamaterials were displayed and analyzed by experiments, theoretical calculation and finite element analysis. The stiffness, energy absorption and vibration damping effects are regulated by varying the structural parameters and temperature field. This multifunctional and tunable metamaterial is expected to be widely applied in related fields such as aerospace engineering and intelligent robots. [Display omitted]